A comparison of Cardiac Triage Method and Emergency Severity Index impact on admission time for acute coronary syndrome patients - Azam Mohammadi Sangsari; Ghanbar Roohi; Zahra Sabzi; Ali Akbar Abdollahi; Naser Behnampour (Golestan University of Medical Sciences, 2023)
Background: Swift diagnosis and treatment of cardiac patients can avert unnecessary hospitalizations. Emergency departments routinely assess patients using the Emergency Severity Index (ESI) method. This study compares the effects of two triage methods, cardiac triage, and ESI, on the admission time of acute coronary syndrome patients. Methods: This intervention study aimed to enhance the quality of therapeutic interventions through an intervention design featuring a control group. The research sample comprised all patients referred to the Sayad Shirazi Educational and Medical Center triage unit in Gorgan, Iran. All patients were randomly allocated into two groups: the control group (23 patients) and the intervention group (46 patients), utilizing a simple random allocation method. The control group underwent triage using the Emergency Severity Index, whereas the intervention group received cardiac triage. Triage forms and time-related indices were completed for both groups. Statistical analysis was conducted using descriptive statistics, the Shapiro-Wilk, and the Mann-Whitney tests to compare these characteristics between the two groups, utilizing SPSS version 18. Results: Significant statistical differences were observed between the two groups in several aspects: the average time from the emergency department to the cardiac intensive care unit (p < 0.001), the average duration of presence of a cardiac specialist physician (p < 0.001), the average time from arrival to triage room exit (p < 0.001), and the average hospitalization time (p < 0.001). These time intervals were shorter in the cardiac triage group. Conclusion: Implementing specialized cardiac triage for cardiac patients plays a pivotal role in reducing response times. Cardiac triage can furnish the medical team with more comprehensive information, thereby improving the management of these patients in the emergency department.